2015
DOI: 10.1080/09168451.2015.1045827
|View full text |Cite
|
Sign up to set email alerts
|

Allyl isothiocyanate induces stomatal closure in Vicia faba

Abstract: Isothiocyanates are enzymatically produced from glucosinolates in plants, and allyl isothiocyanate (AITC) induces stomatal closure in Arabidopsis thaliana. In this study, we investigated stomatal responses to AITC in Vicia faba. AITC-induced stomatal closure accompanied by reactive oxygen species (ROS) and NO production, cytosolic alkalization and glutathione (GSH) depletion in V. faba. GSH monoethyl ester induced stomatal reopening and suppressed AITC-induced GSH depletion in guard cells. Exogenous catalase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…6B and D ). One degradation product of sinigrin, allyl isothiocyanate (AITC), was found to induce stomatal closure in both A. thaliana and V. faba accompanied by ROS and NO production 52 , 92 . AITC-induced cytosolic Ca 2+ oscillation was also observed in A. thaliana guard cells 52 .…”
Section: Discussionmentioning
confidence: 99%
“…6B and D ). One degradation product of sinigrin, allyl isothiocyanate (AITC), was found to induce stomatal closure in both A. thaliana and V. faba accompanied by ROS and NO production 52 , 92 . AITC-induced cytosolic Ca 2+ oscillation was also observed in A. thaliana guard cells 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, additional reverse genetics studies corroborated the role of GLS metabolism in stomatal movement (Islam et al., 2009; Zhu et al., 2014). Furthermore, stomatal closure was induced by pharmacological treatments with different GLS hydrolysis products (Khokon et al., 2011; Sobahan et al., 2015). However, these products and the amounts used are of synthetic origin and abundance.…”
Section: Cell Type-specific Cellular and Subcellular Organization Of mentioning
confidence: 99%
“…The Arabidopsis cyp79b2 / cyp79b3 mutants are known to produce mostly aliphatic GLSs (Zhao et al., 2002; Chen et al., 2003; Grubb and Abel, 2006; Khokon et al., 2011; Sobahan et al., 2015), while the myb28/myb29 mutants are known to produce mostly indolic GLSs (Hirai et al., 2007; Beekwilder et al., 2008). Furthermore, the tgg1/tgg2 double mutant showed undetectable myrosinase activity, and damage-induced breakdown of endogenous GLSs was not from aliphatic GLSs and was greatly slowed for indole GLSs (Barth and Jander, 2006).…”
Section: Cell Type-specific Cellular and Subcellular Organization Of mentioning
confidence: 99%
“…Reactive oxygen species, particularly H 2 O 2 , are important second messengers in guard cell signaling induced by abiotic and biotic factors ( Pei et al, 2000 ; Zhang et al, 2001 ; Khokon et al, 2010a ; Hoque et al, 2012 ; Hossain et al, 2013 ; Ye et al, 2013a ; Kadota et al, 2014 ; Sobahan et al, 2015 ). Researches using leaf disks have provided most of the current knowledge of MAMP-induced H 2 O 2 production.…”
Section: Core Signaling Events Downstream Of Mamp Perception In Guardmentioning
confidence: 99%
“…Another important mechanism involved in H 2 O 2 production in guard cell is mediated by class III peroxidases (PRXs; Figure 1 ). Both internal factors, such as SA ( Mori et al, 2001 ; Khokon et al, 2011 ), isothiocyanates (ITCs; Hossain et al, 2013 ; Sobahan et al, 2015 ) and methylglyoxal ( Hoque et al, 2012 ), and external factors, such as YEL ( Khokon et al, 2010a ), chitosan ( Khokon et al, 2010b ), flg22 ( O’Brien et al, 2012 ), and elf26 ( O’Brien et al, 2012 ), induce H 2 O 2 production mediated by PRXs. Pharmacological and genetic studies further showed that salicylhydroxamic acid (SHAM)-sensitive PRXs but not RBOHD or RBOHF are essential for stomatal closure and H 2 O 2 production in guard cells induced by SA, ITCs, methylglyoxal, chitosan and YEL ( Khokon et al, 2010a , b , 2011 ; Hoque et al, 2012 ; Hossain et al, 2013 ).…”
Section: Core Signaling Events Downstream Of Mamp Perception In Guardmentioning
confidence: 99%